Oral health in Chile, current situation and future challenges - Cartes-Velásquez, Ricardo (2020)
In recent decades, Chile has seen an improvement in its indicators of oral morbidity; that has gone hand in hand with the expansion of coverage in promotion, prevention and dental treatment, prioritizing children, pregnant women and the elderly. Albeit this effort, a very high oral morbidity persists, especially in the population aged 20 to 60 years old, whom have little access to restorative dental care. The Ministry of Health has proposed an ambitious 2018-2030 National Oral Health Plan that pursues the improvement of oral health as well as to reduce inequalities, based on the concepts of equity, intersectionality, citizen participation and inclusion and non-discrimination, thus it materializes in four strategic axes: health promotion and prevention of oral diseases; delivery of quality dental services; human resources development; and research, monitoring and evaluation.